2022
DOI: 10.1155/2022/8637386
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Auricular Point Acupressure for Sleep Disturbance in Women with Breast Cancer: A Randomized Controlled Trial

Abstract: Objectives. The study aimed to evaluate the preliminary effect and efficacy of auricular point acupressure (APA) on the quality of sleep in women with breast cancer who were undergoing chemotherapy. Sample & Setting. We conducted a randomized controlled trial on 68 patients with breast cancer who reported poor sleep quality based on the Pittsburgh Sleep Quality Index (PSQI) scores (>7). Methods & Variables. Participants were randomly assigned to an APA treatment group or a control group. Patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…A growing body of clinical studies have demonstrated that the acupoint massage/APA is emerging as an evidenced-based approach in the management of cancer-related symptoms. For instance, breast cancer patients who experienced 3-weeks of auricular point acupressure (APA) tended to have better sleep quality and reduced sleep disturbance compared with their counterparts [32]. The 4-week of APA conducting can provide relief for breast cancer patients by helping to reduce pain, fatigue, sleep disturbance, and interference with daily activities [14].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of clinical studies have demonstrated that the acupoint massage/APA is emerging as an evidenced-based approach in the management of cancer-related symptoms. For instance, breast cancer patients who experienced 3-weeks of auricular point acupressure (APA) tended to have better sleep quality and reduced sleep disturbance compared with their counterparts [32]. The 4-week of APA conducting can provide relief for breast cancer patients by helping to reduce pain, fatigue, sleep disturbance, and interference with daily activities [14].…”
Section: Discussionmentioning
confidence: 99%
“…As participantes randomizadas para o grupo controle receberam apenas educação sobre higiene do sono de forma verbal e escrita e o grupo experimental recebeu educação em higiene do sono e aplicação de AA nos pontos Shenmen, Coração, Subcórtex, podendo ter mais pontos adicionados (Rim, Estômago, Simpático e possíveis regiões reflexas de dores) de acordo com a necessidade de cada paciente.As medidas foram avaliadas pelo PSQI e por um dispositivo usado no pulso que registra dados relevantes de ritmos circadianos e parâmetros de sono em qualquer situação. A qualidade do sono foi melhor no grupo experimental em relação ao grupo que recebeu educação sobre higiene do sono isoladamente(74). terapêutica isolada eficaz para o transtorno de insônia(75).…”
unclassified